Simulation of fluoride transport in groundwater using visual MODFLOW flex and Human Health Risk Assessment - Sathish Nagaraj; Uma Shankar Masilamani (Applied Water Science)
Abstract Geogenic contamination of fluoride severely impacts groundwater quality rather than industrial contamination. In this study, MODFLOW and MT3D applications are used to predict the groundwater flow and fluoride transport in Vaniyambadi and Ambur taluk in Tirupathur district. The conceptual model with three-layered aquifer system has been developed using visual MODFLOW flex v6.1 for an area of 955 km2, with each grid cell sized 1000 m × 1000 m (51 rows × 49 columns). The model was calibrated from 2021 to 2022 for 30 -day period. Calibration of groundwater flow simulation after 365 days indicates that R 2 value was 0.98; SEE, RMSE and NRMSE were 3.72 m, 27.87 m and 6.33%, respectively. MT3D simulation reveals that the value of R2 was 0.97, and RMSE and NRMSE were 0.23 m and 7.41%, respectively. The calculated fluoride concentration ranges between 0.3 and 3.49 mg/L; after 20 years of prediction, it was found to be 0.35–2.69 mg/L. The source of fluoride contamination is charnockite and granite-gneiss complex rock in Yelagiri Hill, which has 4 mg/L; after 20 years of simulation, the concentration was 9.91 mg/L and the plume extends up to 8 km towards the Palar River basin. Furthermore, HHRA has been used to evaluate the impact of fluoride on adults and children. According to the HHRA, hazard index (HI) was found to be more than one in many locations, causing serious health hazard. The results of these findings pave the way for further research on prevention of groundwater pollution due to geogenic migration.